The Influence of Political Configuration in The Creation of The New KUHP (An Examination of the New Wave of Indonesian Democracy in the Reformation Era) - Fernanda, Vuzio; Patmos, Yan; Syam, Fauzi (Fakultas Syariah INSURI Ponorogo, 2024)
The intervention of political power based on the facts of law enforcement can affect responsive and conservative patterns in the formation of legal products, indicating that certain political situations can produce legal products that are in accordance with their political nature, including in the formation of the new Criminal Code which has become a public concern in Indonesia. This research aims to provide a deeper understanding of the relationship between political structure and the development of criminal law in Indonesia. The method used in collecting legal materials in this research is carried out using library research, namely by using archival review techniques or literature studies of books, journals, articles, theses or works of experts related to the research conducted. The results of this study show that in the current reform era, political configuration has a dominant influence on the structure and substance of law. Political power plays a key role in the formation of laws, where the interests of certain groups often dominate the resulting policies. Legal products are often used as a means of justifying power policies, even though they may contradict the values of public justice and are no longer in accordance with Indonesia's cultural dynamics.